2021
DOI: 10.3390/polym13091375
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epigallocatechin-Gallate-Grafted Chitosan Nanoparticles and Evaluation of Their Antibacterial and Antioxidant Potential

Abstract: Nanoparticles based on chitosan modified with epigallocatechin gallate (EGCG) were synthetized by nanoprecipitation (EGCG-g-chitosan-P). Chitosan was modified by free-radical-induced grafting, which was verified by Fourier transform infrared (FTIR). Furthermore, the morphology, particle size, polydispersity index, and zeta potential of the nanoparticles were investigated. The grafting degree of EGCG, reactive oxygen species (ROS) production, antibacterial and antioxidant activities of EGCG-g-chitosan-P were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Chitin is the second most abundant natural polymer after cellulose [4], and CS is derived from chitin (exoskeletons such as prawns, crustacean shells) via deacetylation reaction; thus, it is normal that CS has received attention from many researchers. CS is easy to obtain and is also a very compatible and effective biomaterial usable for many applications, for example, in the biomedical field [5,6], where it serves as an alternative candidate for drug delivery because it has a regenerative effect on connective tissue [7]. CS is normally associated with a moisture-resistant polymer while maintaining the overall biodegradability of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin is the second most abundant natural polymer after cellulose [4], and CS is derived from chitin (exoskeletons such as prawns, crustacean shells) via deacetylation reaction; thus, it is normal that CS has received attention from many researchers. CS is easy to obtain and is also a very compatible and effective biomaterial usable for many applications, for example, in the biomedical field [5,6], where it serves as an alternative candidate for drug delivery because it has a regenerative effect on connective tissue [7]. CS is normally associated with a moisture-resistant polymer while maintaining the overall biodegradability of the product.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EGCG possessed a higher number of -OH groups, followed by CAT. As a result, their bulky structures limited the solubility in the aqueous medium and caused steric hindrance, thus restricting hydrogen bonding with COS molecules [ 21 ]. This was supported by the lowest conjugation efficiency of EGCG and CAT at 10 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be concluded that malic acid, chlorogenic acid, epigallocatechin gallate, quercetin, ellagic acid, and pyrogallol are the chief phenolic compounds that might be accountable for the observed antioxidant potential of the selected plant. In other studies, it has been reported that these compounds, chlorogenic acid [30], epigallocatechin gallate [31], quercetin [32], ellagic acid [33], pyrogallol [34] have potent antioxidant effects. A total of 273 compounds are reported from the seven Alnus species (A. japonica, A. hirsuta, A. glutinosa, A. incana, A. nepalensis, A. sieboldiana and A. firma), with very little or no attention being paid to alternative folks uses of those plants.…”
Section: Discussionmentioning
confidence: 99%